PERSEPSI ORANG MUDA KATOLIK PAROKI MATER DEI TENTANG MERAYAKAN HARI MINGGU SEBAGAI HARI TUHAN - Don Bosco Karnan Ardijanto; Meiry Chrimiyati (Bahasa Indonesia, 2018)
Sunday was a very special day to get together with our brothers and sisters in the Church, to give thanks to God and the memory of the passion, resurrection andglory of the Lord Jesus. In addition, Sunday is recommended as a day to develop the piety of the faithfull, as a day of excitement and a day free from work. There is a reason that is not the right of the people to go to church on Sunday or not. First, they come out of habit. Second, there are people who think that they can pray better if done at home alone, so no need to go to church on Sundays. Of these concerns, researched "Youth Perceptions of Mater Dei Catholic Parish of Celebrating Sunday as the Lord's Day”. In particular, the research carried out at Mater Dei parish Madiun. Results using qualitative methods. The purpose of this paper is to understand the meaning of the celebration of Sunday. Knowing the young people's perception of Mater Dei Catholic parish on Sunday celebration. Knowing the various forms or ways Catholic Youth Mater Dei parish celebrated Sunday. From the results it can be concluded that the people of Mater Dei Catholic parish actually been very understanding about the meaning of Sunday and the activities of Catholics on Sunday to go to church, it's just that there are a few do not realize to follow the activities of the Church on Sundays.